Crystal Structures of Two Macrocyclic Bischalcones Possessing 26-Membered Rings. (5th August 2015) - Mondal, Rina; Sepay, Nayim; Ghoshal, Debajyoti; Mallik, Asok K.
Abstract : Single crystal X-ray diffraction of two macrocyclic bischalcones, namely, (2 E, 25 E )-11, 17, 33, 37-tetraoxapentacyclo[36.4.0.0 5, 10 .0 18, 23 .0 27, 32 ]dotetraconta-1(42), 2, 5, 7, 9, 18, 20, 22, 25, 27, 29, 31, 38, 40-tetradecaene-4, 24-dione(1 ) and (2 E, 24 E )-11, 16, 32, 37-tetraoxapentacyclo[36.4.0.0 5, 10 .0 17, 22 .0 26, 31 ]dotetraconta-1(42), 2, 5, 7, 9, 17, 19, 21, 24, 26, 28, 30, 38, 40-tetradecaene-4, 23-dione(2 ), each containing a 26-membered ring, has been studied. Compound1 belongs to the monoclinic system, space group C2/c with a = 34.3615(9) Å, b = 12.7995(3) Å, c = 14.6231(3) Å, β = 96.912(2)°,    V = 6, 384.6(3) Å 3, and Z = 8. Compound2 is triclinic, space group P-1 with a = 10.066(2) Å, b = 10.670(3) Å, c = 16.590(3) Å, α = 85.95(2), β = 89.244(14), γ = 62.211(13), V = 1572.0(6) Å 3, and Z = 2. Intermolecular C–H⋯O hydrogen bonding interactions are present in both compounds.